Perceptions of clinical pharmacy specialists' contributions in mental health clinical teams - Chris Gillespie, PhD; Felicia Kleinberg, MSW; Anna Zogas, PhD; Anthony Morreale; Heather Ourth, PharmD; Michael Tran, PharmD; Tera Moore, PharmD; Donald Miller, ScD; Megan McCullough, PhD (American Association of Psychiatric Pharmacists, 2022)
Introduction: Mental health (MH) clinical pharmacy specialists (CPS) are increasingly functioning as integral providers in MH care teams. MH providers may delegate many medication management tasks to the CPS. As there is a shortage of primary care and specialist MH providers, CPS are increasingly being utilized in MH care clinics. We assess provider and CPS perceptions of the contributions of CPS to MH clinical teams in the Veterans Health Administration. Methods: We examined the roles and functions of CPS in MH clinics through surveys (n=374) and semistructured interviews (n=16) with MH CPS and other members of MH clinical teams (psychiatrists, nurse practitioners, registered nurses, social workers) to gain insight into how CPS were integrated in these settings. We assessed perceptions of CPS contributions to MH teams, interactions between CPS and other providers, and challenges of integrating CPS into MH clinical teams. Results: Contributions of CPS in MH were received positively by clinical team members. Clinical pharmacy specialists providing comprehensive medication management were especially valuable in the management of clozapine. The knowledge and training of CPS reassured providers who frequently referred to them with questions about medication and medication therapy management. MH CPS were also perceived to be received well by patients. Discussion: The integration of MH CPS into MH teams was well received by team members and patients alike. The MH CPS have become important members of the MH team and are widely viewed as being able to improve access, quality, and workflow.